PENGARUH RASIO DIAMETER PIPA TERHADAP PERUBAHAN TEKANAN PADA BERNOULLI THEOREM APPARATUS - Aufa, Ahmad; Rubiono, Gatut; Mujianto, Haris (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2016)
Bernoulli theorem can applied to many devices such as ventury tube in aoutomotivecarburetor, venturimeter, pitot tube, chimney and aeroplane wings. This research is aimed to get the effect of diameter ratio due to pressure different in Bernoulli theorem apparatus. The research is conduct by experiment using fluid flow circuit. Diameter ratio is varied as 0,67; 0,50 and 0,33. Fluid flow rate is varied by valve opening arrangement as 45o, 60o, 90o. Measurements are done at7 measurement point by U type manometer. Volume flow rate is measured by flowmeter and stopwatch. The research shows that diameter ratio has effect due to pressure changes. theincrease of diameter ratio tend to increase the pressure. Maximum pressure is happen at 0,67 diameter ratio; 0,0192 lt/s volume flow rate at first measurement point. Minimum pressure is happen at 0,33 diameter ratio; 0,0247 lt/s volume flow rate at fifth measurement point.